The Interface of Explicit and Implicit Knowledge in a Second Language: Insights From Individual Differences in Cognitive Aptitudes. Issue 4 (18th May 2017) - Suzuki, Yuichi; DeKeyser, Robert
Abstract: Recent research has called for the use of fine‐grained measures that distinguish implicit knowledge from automatized explicit knowledge. In the current study, such measures were used to determine how the two systems interact in a naturalistic second language (L2) acquisition context. One hundred advanced L2 speakers of Japanese living in Japan were assessed using tests of automatized explicit knowledge and implicit knowledge, along with tests of phonological short‐term memory and aptitude tests for explicit and implicit learning. Structural equation modeling demonstrated that aptitude for explicit learning significantly predicted acquisition of automatized explicit knowledge, and automatized explicit knowledge significantly predicted acquisition of implicit knowledge. The effects of implicit learning aptitude and phonological short‐term memory on acquisition of automatized explicit knowledge and implicit knowledge were limited. These findings provide the first empirical evidence that automatized explicit knowledge, which develops through explicit learning mechanisms, may impact the acquisition of implicit knowledge. Open Practices: This article has been awarded an Open Materials badge. All original materials are publicly accessible in the IRIS digital repository athttp://www.iris-database.org . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .